he fair play, the victory and the gender issue in football in the context of primary education - Cabañero García, M.; Velázquez Buendía, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Football is a social, cultural, mediatic and economic phenomenon. There is a great deal of research on its influence on who practices it. However, the objective of this research was to explore its influence on social values related to fair play, gender equality and the means-ends relation, in elementary students, as aspects that can be reflected in some social problems. The study population was students of sixth grade. It is a cross-sectional descriptive study. The sources of information used were a questionnaire and a discussion group. The results indicated that gender and federated soccer practice influence fair play, a desire for victory and gender equality, being boys and students practicing soccer more prone to anti-fair behavior, more result-focused and with a more negative view towards the figure of women in football.